2020
DOI: 10.7717/peerj.8416
|View full text |Cite
|
Sign up to set email alerts
|

Remarks onMastigodiaptomus(Calanoida: Diaptomidae) from Mexico using integrative taxonomy, with a key of identification and three new species

Abstract: Background In Mexico, species of four families of free-living calanoid copepods have been recorded as inhabitants of several freshwater systems. These families are Centropagidae, Temoridae, Pseudodiaptomidae and Diaptomidae. The genera Leptodiaptomus and Mastigodiaptomus are the most speciose diaptomid genera in Mexico, and they inhabit natural and artificial lakes, ephemeral ponds, springs, and caverns. Leptodiaptomus is considered as an endemic Nearctic genus, whereas Mastigodiaptomus is a widely distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…We consider that detailed morphological analysis and the use of molecular tools, like DNA barcoding, will help to uncover the real identity of all these species, as the case presented here or with Scapholeberis duranguensis Quiroz-Vazquez & Elías-Gutiérrez, 2009, which was initially cited as S. rammneri by DeWaard et al (2006) and for which the closest species was S. freyi. The GMYC model used as a species delimitation method has been tested in other crustaceans as copepods (Gutierrez-Aguirre et al, 2020). It has been consequent with other methods as the BIN system and morphology, giving strong support to the modern description of species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We consider that detailed morphological analysis and the use of molecular tools, like DNA barcoding, will help to uncover the real identity of all these species, as the case presented here or with Scapholeberis duranguensis Quiroz-Vazquez & Elías-Gutiérrez, 2009, which was initially cited as S. rammneri by DeWaard et al (2006) and for which the closest species was S. freyi. The GMYC model used as a species delimitation method has been tested in other crustaceans as copepods (Gutierrez-Aguirre et al, 2020). It has been consequent with other methods as the BIN system and morphology, giving strong support to the modern description of species.…”
Section: Discussionmentioning
confidence: 99%
“…The best fit substitution model was TIM2+G, and it was replaced by GTR+G in MrBayes along with 1 M generations to obtain a tree. The Generalized Mixed Yule Coalescent (GMYC) method was applied as Gutierrez-Aguirre et al (2020) suggested to delimit the species. Finally, with the groups delimited by the GMYC technique, we calculated the mean estimates of evolutionary divergence over sequence pairs between groups.…”
Section: Methodsmentioning
confidence: 99%
“…From 1915 to 1997 cladocerans presented the highest species richness with 7 known species, followed by 3 calanoid copepods reported: A. dorsalis, Mastigodiaptomus albuquerquensis, and the endemic M. amatitlanensis [6,9,12,15]. This latter species is considered as a possibly extinct [16], because since its description date by Wilson (1941) [15] it has not been recorded, including this study. Additionaly we report for the first time in Amatitlán lake, two cyclopoid copepods, considered as exotic species for America: Thermocyclops crassus (Euro-Asiatic species) and M. thermocyclopoides (Afro-Asiatic species) [22,25].…”
Section: Actual Recordsmentioning
confidence: 91%
“…With a historical and actual review of zooplankton biodiversity as well as an actual knowledge of the environmental conditions, we present the distribution, species richness, and spacial and temporal abundance of zooplankton and its relationship with environmental variables. We report the occurrence of two cyclopoid exotic species (Mesocyclops thermocyclopoides (Fischer, 1853) and Termocyclops crassus Harada, 1931) and the absence of the calanoid copepod Mastigodiaptomus amatitlanensis (Wilson, 1941) that was used to be recorded as endemic of the lake [15,16]…”
Section: Introductionmentioning
confidence: 99%
“…We do not know anything about the biology of any zooplankter in this region. However, it was recently detected an apparent genetic structure in the haplotypes of M. siankaanensis from the center to the south of Yucatan [58], being different haplotypes and possibly in the process of differentiation.…”
Section: Species Composition Comparisonmentioning
confidence: 99%